Qualitative versus quantitative research strategies: contrasting epistemological and ontological assumptions - Bahari, Siti Fatimah (Penerbit UTM Press, 2010)
This paper attempts to discuss how qualitative (intensive) and quantitative (extensive) research strategies differ by contrasting epistemological and ontological aspects and how these beliefs and views fit with their different intellectual goals. Firstly, this paper discusses the importance of understanding philosophy in social science research and its relation to qualitative (intensive) and quantitative (extensive) research strategies. Then it develops by contrasting these two types of research strategies in relation to the principle orientation to the role of theory, epistemological and ontological assumptions. Epistemological assumptions consist of interpretivism for qualitative (intensive) research strategies and positivism for quantitative (extensive) research strategies. Whereas ontological assumptions constitute subjectivism/constructivism for qualitative (intensive) research and objectivism for quantitative (extensive) research strategies. Further it will explain how these two types of research strategies fit the different intellectual goals and finally concludes by discussing an alternative research strategi namely mixed method that may be employed in social science research.